Avaliação funcional e da qualidade de vida de pacientes submetidos à discopexia da articulação temporomandibular - Zanin, Roberto Ferreira (2021)
Temporomandibular disorders (TMD) and their treatment have a physical and psychological impact on quality of life (QOL). This study aimed to assess the impact of oral health on QOL by evaluating 35 patients (70 discs) with bilateral anterior disc displacement without reduction preoperatively (T0), 21 days (T1) and 6 months (T2) after surgery for anterior disc repositioning and anchoring. Oral health-related QOL was assessed using the short form of the Oral Health Impact Profile (OHIP-14), Helkimo Index and pain evaluation using VAS (Visual Analogic Scale). The OHIP-14 scores significantly decreased in evaluation between time in all domains and, also with the total domains of OHIP-14 (P <0.001). An evident improvement in quality of life was observed in patients under 20 years old (p = 0.024), 20 to 40 years old (p> 0.001) and over 40 years old (p> 0.001), where they evolved from severe dysfunction (T0) to moderate dysfunction after 21 days (T1) and then for mild dysfunction at the end of the evaluation (T2). All age groups showed improvement in pain over time according to the VAS scale under 20 years (p = 0.006), 20 to 40 years and above 40 years (p> 0.001). The results suggest that TMD affect individuals in many aspects of their lives and that general or condition-specific oral health-related QOL measures are valuable tools for determining the impact of joint disorders on patients’ QOL. Surgical treatment for articular disc repositioning and anchoring had a positive impact on patients’ QOL.